Assessing Individual Differences in Mental Load: Eye-Tracking Insights for Adaptive Learning - Bend, Julia; Öörni, Anssi (International Journal of Advanced Corporate Learning (iJAC), 2025)
This study explores individual differences in working memory and perceptual load, with a particular focus on sex-related variations, to improve adaptive technology-enhanced learning. Using eye-tracking metrics, such as fixation duration and fixation rate, the research highlights how these measures can provide actionable insights for personalizing learning environments. The results reveal significant sex-related differences: females exhibited shorter fixation durations and higher fixation rates, reflecting elevated perceptual load, while males demonstrated longer fixation durations and greater efficiency in handling cognitively demanding tasks. These findings suggest that sex differences in cognitive processing influence task performance and engagement, underscoring the need to consider such variations in educational design. By integrating fixation-based metrics, TEL systems can adapt content dynamically to align with learners’ cognitive profiles, fostering more inclusive and effective learning experiences. The study also advocates for training transferable skills, such as attention switching, to enhance learners’ ability to manage perceptual load.